Studi Komparatif Pengembangan Contact Tracing Applications Di Singapura dan Indonesia (Studi Kasus: TraceTogether dan PeduliLindungi): (Case Study: TraceTogether and PeduliLindungi) - Diah Khrisma Putriana; Aditya Putra Pratama Santosa; Inge Dhamanti (State Islamic University of Sunan Ampel, 2022)
One way to handle the COVID-19 pandemic is tracing related to close contacts of positive cases. This is to identify the place and time of people who have close contact with positive COVID-19 patients and inform those indicated as positive for COVID-19 to prevent further spread. Therefore, each country has released Contact Tracing Applications (CTAs) to support the tracing process. TraceTogether and PeduliLindungi applications are examples of embodiments of Contact Tracing Applications. This study aimed to compare the development of CTAs in Singapore and Indonesia to deal with the COVID-19 pandemic. This research used a literature research method to manifest the development of CTAs in Singapore and Indonesia. His study focused on the differences in application development that have been implemented in the two countries: Singapore as a pioneer of CTAs with the TraceTogether application and Indonesia which Singapore inspired by designing the PeduliLindungi application. This research is expected to be considered in the development of better CTAs. This is one of the recovery steps for the two countries after the COVID-19 pandemic in approaching health through the application.